Microwave absorption behavior of a polyaniline magnetic composite in the X-band - Aphesteguy, J.C.; Damiani, A.; DiGiovanni, D.; Jacobo, S.E. (Physica. B, Condensed matter, 2012)
The development of nanosized materials is a subject of considerable interest both for understanding of the fundamental properties of magnetic materials for new technological applications. Polyaniline, composites Fe3O4/(PANI) with conducting, magnetic and electromagnetic properties with different amounts of Fe3O4 were successfully prepared. The samples were structurally characterized by scanning electron microscopy (SEM), X-ray diffraction and transmission electron microscopy (TEM) and magnetically, with a superconducting quantum interference device (SQUID) magnetometer. In order to explore microwave-absorbing properties in X-band, the composite nanoparticles were mixed with an epoxy resin to be converted into a microwave-absorbing composite. Microwave behavior with different Fe3O4/(PANI)-epoxy resin ratio was studied using a microwave vector network analyzer (VNA) in the range 7.5 to 13GHz. For a constant thickness of 1.5mm, absorption increases with the magnetite contents in the composites and in the oriented samples by the application of a magnetic field.